2008
DOI: 10.1029/2007jd009302
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation mode particles in upslope valley winds at Mount Norikura, Japan: Implications for the vertical extent of new particle formation events in the lower troposphere

Abstract: Number‐size distributions of atmospheric aerosol particles of 9–300 nm diameter were observed along with SO2 and NH3 concentrations at Mount Norikura, Japan (36.1°N, 137.5°E, 2770 m asl), during September 2001 and August–September 2002. Particle size distributions between the free troposphere and the mixed layer were measured at the site under local wind system conditions, comprising downslope mountain and upslope valley winds. The local wind system was well developed under clear‐sky conditions and was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 53 publications
3
28
1
1
Order By: Relevance
“…For example, Venzac et al (2008) reported growth rates of 1.8±0.7 nm h −1 in the Nepalese Himalayas at an elevation of 5079 m a.s.l., thus slightly smaller than found in this study. On contrary Nishita et al (2008) reported growth rates of 2.6-3.1 nm h −1 in Mt. Norikura, Japan at altitude of 2770 m and Venzac et al (2009) 4.7-5.6 nm h −1 in Puy de Dôme, France at an elevation of 1465 m. The growth rates obtained here, fit right on top of the ones from Japan which were measured approximately at the same elevation.…”
Section: Discussionmentioning
confidence: 54%
“…For example, Venzac et al (2008) reported growth rates of 1.8±0.7 nm h −1 in the Nepalese Himalayas at an elevation of 5079 m a.s.l., thus slightly smaller than found in this study. On contrary Nishita et al (2008) reported growth rates of 2.6-3.1 nm h −1 in Mt. Norikura, Japan at altitude of 2770 m and Venzac et al (2009) 4.7-5.6 nm h −1 in Puy de Dôme, France at an elevation of 1465 m. The growth rates obtained here, fit right on top of the ones from Japan which were measured approximately at the same elevation.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies conducted at mountain sites have shown a diurnal pattern of changes between air coming from the planetary boundary layer (PBL) during the day and from the free troposphere (FT) during the night (Nyeki et al, 1998b;Shaw, 2007;Nishita et al, 2008). A diurnal pattern in the vertical wind speed at Mount Waliguan has also been reported (Wang et al, 2006).…”
Section: Temporal Variationmentioning
confidence: 95%
“…Shaw (2007) compared the difference in the potential temperature between mountain observations and observations conducted at the mountain base. Nyeki et al (1998b) and Nishita et al (2008) used synoptic or local meteorological conditions as criteria for selection. Besides these methods, also water vapor pressure and concentrations of some relatively long-lived trace gases produced in PBL, such as CO, could be useful criteria when looking at the type of air.…”
Section: Temporal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, at a study site on Mt. Norikura in Japan NH 3 was measured using an acid-impregnated filter and found no positive correlation between [NH 3 ] and NPF for NH 3 at the sub-ppbv level [Nishita et al, 2008]. Other NH 3 measurements for NPF studies include the Hyytiälä measurements with a refluxing mist chamber [Riipinen et al, 2007].…”
Section: Introductionmentioning
confidence: 99%